Environmental effects on cognitive abilities - Sternberg, Robert J.; Grigorenko, Elena L. (L. Erlbaum Associates, 2001)
This volume discusses how the environment influences the development and the maintenance of cognitve abilities. This discussion is important because genes always have their effect in correlation with the environment and we can control the environment, at least to some extent.